Electrolytic aluminum anode high-conductivity high-temperature anti-oxidation life-prolonging coating as well as preparation method and application thereof
By spraying high-conductive high-temperature anti-oxidation and life-extended coatings composed of refined bauxite, silicon carbide, graphene and other materials on the surface of electrolytic aluminum anode carbon blocks and steel claws, the problem of serious loss of the anode in a high-temperature oxidation environment is solved, and the problem of serious loss of the anode in a high-temperature oxidation environment is achieved. The effect of reducing energy consumption and extending service life.
Patent Information
- Application Number
- CN202411501074.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-25
AI Technical Summary
The electrolytic aluminum anode carbon block and steel claws are seriously damaged in high-temperature oxidation environments, resulting in high production energy consumption and low output. The existing nano high-temperature anti-oxidation coating preparation process is complex and has poor conductivity, easy cracking and does not have self-healing ability.
采用由精炼铝土矿、碳化硅、石墨烯、钠长石、滑石和镧系氧化物组成的高导电高温防氧化延寿涂料,通过球磨和加热处理提高涂层的力学和导电性能,并在阳极 The surface of the carbon block and steel claws is sprayed to prevent oxidation.
It effectively reduces the high-temperature oxidation loss of the anode carbon block and steel claws, improves the conductivity, extends the service life, simplifies the preparation process, reduces production energy consumption, and ensures the purity of the aluminum liquid.
Smart Images

Figure CN119286288A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of new metallurgical materials, and specifically relates to a high-conductivity, high-temperature, anti-oxidation and life-extending coating for electrolytic aluminum anodes and a preparation method thereof, and also relates to the application of the high-conductivity, high-temperature, anti-oxidation and life-extending coating for electrolytic aluminum anodes. Background Art
[0002] Anode carbon blocks refer to carbon blocks produced with petroleum coke and asphalt coke as aggregates and coal tar as binder, and are used as anode materials for prebaked aluminum electrolytic cells. In the process of aluminum electrolysis, the anode has to withstand the high temperature brought by molten aluminum oxide for a long time, as well as the oxidizing environment brought by carbon dioxide, hydrogen fluoride, cryolite, oxygen and atomic oxygen produced at high temperatures, which leads to continuous loss of anode carbon blocks within a working cycle, resulting in slag falling, hot tanks, cathode damage, increased energy consumption, low yield, impure products and other problems. Existing methods to solve this problem include improving the purity of anode carbon blocks, spraying a protective layer on the surface of the anode, etc. Among them, spraying a protective layer has the advantages of low cost and good effect.
[0003] Anode steel claws for electrolytic aluminum, also known as electrolytic claws, are core components of electrolytic aluminum equipment. They are mainly used to connect anodes and transmit current. When casting this component, in order to save costs, low-carbon cast steel materials are usually used as the main component, and a part of scrap steel claws will be added for reuse. The selection of this material is intended to ensure that the anode steel claw has good electrical conductivity while reducing costs. However, during the electrolytic aluminum process, the anode steel claw will be exposed to electrolytes, electrode materials, air and electrolytic flue gas. These substances contain moisture and other chemical components, which will react chemically with the steel claw under high temperature conditions to form oxides, causing corrosion of the steel claw. Especially when the temperature in the electrolytic cell reaches above 100°C, the adsorbed moisture evaporates into water vapor, escaping from holes and gaps from bottom to top, causing corrosion of the steel claw. At the same time, during the electrolytic aluminum production process, the anode steel claw will be damaged by thermal stress, electromagnetic force and collision force, which will cause the steel claw to deform, damage, and even crack or fall off, thus affecting its service life. Moreover, the raw materials for the production of anode steel claws are mostly scrap steel, miscellaneous steel and scrapped steel claws, which leads to large fluctuations in the content of alloy elements, especially the excessive content of impurity elements such as C, S, and P, which will increase the resistance of the steel claws. In addition, the unreasonable casting process in the production process can easily lead to defects such as shrinkage cavities, shrinkage, and inclusions inside the steel claws, reducing the effective conductive area and further increasing the resistance. These factors work together to increase the resistivity of the anode steel claws, affecting their conductive properties and service life.
[0004] In some existing solutions, nano-high temperature anti-oxidation coatings specially used for electrolytic aluminum anodes are used to protect anode carbon blocks. However, the nano-high temperature anti-oxidation coatings used often have complicated preparation processes and complex raw material ratios, and the conductivity of the enhanced coatings is poor, which easily leads to increased energy consumption, and thus production capacity cannot be fully utilized. In addition, the coating is also prone to cracking under high temperature oxidation conditions and does not have self-healing ability, causing the surface of the anode carbon block and the steel claw to be exposed to the high temperature oxidation environment again; there are also some solutions that fill the cracks in the coating by adding special ingredients to the coating, but the added ingredients are easy to react with the aluminum liquid, resulting in aluminum liquid pollution or reduced production.
[0005] Based on this, an electrolytic aluminum anode coating is provided, which can protect the anode carbon block and the anode steel claw from oxidation and reduce loss as much as possible, while simplifying the preparation process, reducing the preparation cost, and improving the conductivity to reduce production energy consumption. This is of great significance to the development of low energy consumption and high output in the electrolytic aluminum industry, and is also a technical problem that needs to be solved urgently. Summary of the invention
[0006] One of the purposes of the present invention is to provide a highly conductive, high-temperature anti-oxidation and life-extending coating for electrolytic aluminum anodes that can protect anode carbon blocks and anode steel claws to avoid loss of both due to high-temperature oxidation, and can also improve conductivity to reduce production energy consumption.
[0007] The second object of the present invention is to provide a method for preparing a coating for electrolytic aluminum anode with high conductivity, high temperature, anti-oxidation and life extension.
[0008] The third purpose of the present invention is to provide a high-conductivity, high-temperature, anti-oxidation and life-extending coating for electrolytic aluminum anodes for use in the electrolytic aluminum industry.
[0009] The technical solution adopted by the present invention to achieve one of the purposes is: to provide a coating for electrolytic aluminum anode with high conductivity, high temperature, anti-oxidation and life extension, which is composed of the following raw materials in parts by weight: 34-50 parts of refined bauxite; 20-25 parts of water; 20-30 parts of silicon carbide; 1.5-3 parts of graphene; 4-6 parts of glaze former; 2.1-2.2 parts of film former; 0.3-0.4 parts of modifier; The glaze former consists of albite, talc and lanthanide oxides; the content of lanthanide oxides in the glaze former is 0.3 wt.%-0.7 wt.%.
[0010] The general idea of the present invention is as follows: The high-conductivity, high-temperature, anti-oxidation and life-extending coating for electrolytic aluminum anode provided by the present invention uses refined bauxite as a basic component and silicon carbide as a main reinforcing component. Silicon carbide can not only refine the grains of aluminum oxide to achieve the purpose of fine grain strengthening, but also silicon carbide, as a material with Mohs hardness second only to diamond, has excellent mechanical properties and can strengthen the mechanical properties of the coating to a certain extent. In addition, silicon carbide, as a semiconductor material, has a certain promoting effect on the passage of anode current, which is beneficial to reducing energy consumption.
[0011] Graphene is used as an auxiliary reinforcement component. Since the carbon atoms in graphene are sp2 hybridized, there is an electron in one of the 2p orbitals that is not involved in the hybridization. Due to the presence of unhybridized electrons in the 2p orbital, a large π bond similar to that in benzene is formed. These π electrons can move freely. At the same time, it has a Dirac cone structure, and the energy states of electrons and holes are very close, so that the electrons in graphene can move at a very high speed. Therefore, it has good conductivity and can effectively improve the conductivity of the coating to reduce energy consumption. At the same time, due to the excellent mechanical properties of graphene, the adhesion, thermal stability and fracture toughness of the coating are improved. In addition, graphene itself has certain lubrication properties. Doping with graphene is conducive to improving the friction resistance of the coating surface and reducing the adhesion of electrolytes on the coating and anode.
[0012] A mixture of albite and talc is used as the main component of the glaze-forming agent. The two can form a glaze at high temperature, which fills the cracks caused by uneven heating or the thermal expansion coefficient of the basic structural phase of the coating being inconsistent with the anode steel claw or carbon block to a certain extent, reduces the contact between the anode carbon block and the surrounding oxidizing atmosphere, and thus reduces the loss of the anode. A small amount of lanthanide oxide is also added to the glaze-forming agent. The addition of rare earth elements allows the alumina of the ceramic-based continuous phase to form a solid solution, promotes the refinement of alumina grains, and improves adhesion, thermal stability and fracture toughness. At the same time, the addition of rare earth elements also plays a certain strengthening role on the coating.
[0013] Furthermore, the content of aluminum oxide in the refined bauxite is 97wt.%-99wt.%. Compared with aluminum oxide, refined bauxite is inevitably mixed with certain impurity elements (such as iron, gallium, calcium, magnesium, silicon, etc.) during the extraction of aluminum oxide. These elements are similar to the constituent elements of albite and talc, and can complement each other and improve the crack filling effect.
[0014] Furthermore, the composition of the glaze forming agent is 32.5%-47.5% of talc, 52.5%-67.5% of albite powder, and 0.3%-0.7% of lanthanide oxide by weight percentage. In the glaze forming agent used in the present invention, talc and albite can form a glaze at high temperature to fill the cracks formed on the surface of the steel claw coating, and the substance forming the glaze does not react with the aluminum liquid, thereby avoiding pollution to the aluminum liquid.
[0015] Furthermore, the lanthanide oxide is in powder form, and can be directly obtained from commercial products or prepared from xenotime. The lanthanide oxide includes a combination of one or more of lanthanum oxide, cerium oxide, neodymium oxide, and europium oxide.
[0016] Preferably, the preparation method of lanthanide oxides comprises: acid leaching xenotime to obtain a solution containing lanthanide ions; adding alkali solution to the solution to obtain a precipitate, and heat treating the precipitate to obtain lanthanide oxides. The lanthanide oxides used in the present invention are prepared by acid leaching, alkali solution precipitation and calcination decomposition of xenotime as a raw material. This method can not only effectively separate lanthanide elements, but also has the advantage of low cost.
[0017] Furthermore, the modifier is selected from a silane coupling agent or sodium dodecylbenzene sulfonate. Preferably, the modifier is 3-(methacryloyloxy)propyltrimethoxysilane (silane coupling agent KH-570).
[0018] Furthermore, the film-forming agent is selected from one of polyurethane, polyacrylate and polyvinyl pyrrolidone. Preferably, the film-forming agent is selected from polyvinyl pyrrolidone, which contains a nitrogen atom heterocycle and a ketone carbonyl containing an oxygen atom in its structure, has a strong effect on the silane coupling agent and other inorganic components, and can effectively form a film on the anode steel claw and / or the anode carbon block with strong adhesion.
[0019] The technical solution adopted by the present invention to achieve the second purpose is: to provide a method for preparing the coating according to one of the purposes of the present invention, comprising the following steps: S1, ball-milling the refined bauxite, mixing the ball-milled product with a modifier, and coating and modifying the product to obtain a first product; S2, mixing the first product with silicon carbide and graphene, and subjecting the mixture to ball milling to obtain a second product; S3, mixing the film-forming agent with water to obtain a film-forming agent solution; mixing albite and talc, crushing and ball-milling to obtain a third product; S4, mixing the second product, the third product and lanthanide oxide powder and adding the mixture to a film-forming agent solution to obtain a fourth product; S5. Place the fourth product in a sealed pressurized environment, heat and mix for a certain period of time, and obtain a coating for electrolytic aluminum anode with high conductivity, high temperature, anti-oxidation and life extension.
[0020] Furthermore, in step S1, the ball-to-material ratio of the ball milling treatment is 5:1, and zirconium oxide grinding balls with diameters of 5 mm, 7 mm and 12 mm are mixed in a quantitative ratio of (15-20): (4-6): (2-3) as ball milling media. The ball milling treatment time is 2.5-4.5 h, and the particle size of the first product is 450-600 mesh.
[0021] Furthermore, in step S1, a powder modifier is used for coating modification, and the modification time is 1-2 hours.
[0022] Furthermore, in step S2, the ball-to-material ratio of the ball milling treatment is 8:1, and zirconium oxide grinding balls with diameters of 1.4 mm, 1.6 mm and 2.5 mm are mixed in a quantitative ratio of (40-55): (15-23): (3-7) as ball milling media. The ball milling treatment time is 4-6 h, and the particle size of the second product is 650-750 mesh.
[0023] Furthermore, in step S3, a roller crusher is first used to continuously crush the product at a power of 25-35 kW for 1-2 hours, and then the crushed product is ball-milled. The ball-to-material ratio of the ball-milling treatment is 3:1. Stainless steel grinding balls with diameters of 6 mm, 8 mm and 10 mm are mixed in a quantitative ratio of (10-12): (4-6): (0.6-1) as ball-milling media. The ball-milling treatment time is 0.5-1.5 hours, and the particle size of the third product is 750-950 mesh.
[0024] Furthermore, in step S5, the pressure is 1.2-1.5 MPa, the heating temperature is 130-170° C., the mixing stirring speed is 50-70 r / min, and the heating time is 2.5-3.5 h.
[0025] The technical solution adopted by the present invention to achieve the third purpose is: to provide an application of a high-conductivity, high-temperature, anti-oxidation and life-extending coating for electrolytic aluminum anodes, wherein the coating is the coating described in one of the purposes of the present invention, or the coating prepared by the preparation method described in the second purpose of the present invention.
[0026] Furthermore, the application includes: attaching the coating to the surface of the anode carbon block and / or the anode steel claw by spraying.
[0027] Furthermore, the coating thickness of the coating on the surface of the anode carbon block is 0.7-1.1 mm, and the coating thickness of the coating on the surface of the anode steel claw is 0.5-0.9 mm.
[0028] Preferably, the coating is sprayed onto the surface of the anode carbon block and the anode steel claw. The anode carbon block is made of anthracite and metallurgical coke as main raw materials and coal tar as a modifier; the anode steel claw is made of low-carbon steel and waste steel claws by melting and casting.
[0029] The high-conductivity, high-temperature anti-oxidation and life-extending coating for the electrolytic aluminum anode provided by the present invention is coated on the surfaces of the anode carbon block and the anode steel claw at the same time, which can protect the anode carbon block and the anode steel claw to avoid loss of both due to high-temperature oxidation during the electrolytic aluminum process, and can also improve conductivity to reduce production energy consumption.
[0030] Furthermore, the coating provided by the present invention is applied to the surface of the anode steel claws cast with low-carbon steel and scrap steel claws as raw materials, which can make up for the defects of low-cost steel claws in poor oxidation resistance and high temperature resistance: on the one hand, the coating can isolate moisture and other chemicals in the high-temperature oxidation environment to prevent corrosion caused by the anode steel claws; on the other hand, the coating with self-repairing function can improve the high temperature resistance of the anode steel claws to prevent them from being deformed, damaged or cracked under the action of thermal stress, electromagnetic force and collision force; in addition, the addition of graphene in the coating also improves the electrical conductivity, making up for the defects of increased resistivity and poor electrical conductivity caused by impurity elements in the scrap steel claw raw materials. The coating improves the comprehensive performance and application performance of the anode steel claws, prolongs its service life, reduces the energy consumption of electrolytic aluminum production and ensures the purity of aluminum liquid.
[0031] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention provides a highly conductive, high-temperature, anti-oxidation and life-extending coating for an electrolytic aluminum anode, wherein a certain proportion of silicon carbide and graphene are added to the coating to enhance the mechanical properties and conductive properties of the coating; a glazing agent with albite and talc as main components is added, and the two can form a glaze surface at high temperature, which to a certain extent fills the cracks caused by uneven heating or the inconsistency between the thermal expansion coefficient of the basic structural phase of the coating and the anode steel claw or carbon block, reduces the contact between the anode carbon block and the surrounding oxidizing atmosphere, and thus reduces the loss of the anode; in addition, a small amount of lanthanide oxide is added to the glazing agent, and the addition of rare earth elements causes aluminum oxide to form a solid solution, promotes the refinement of aluminum oxide grains, and improves adhesion, thermal stability and fracture toughness. At the same time, the addition of rare earth elements also plays a certain strengthening role on the coating.
[0032] (2) The present invention provides a highly conductive, high-temperature, anti-oxidation and life-extending coating for electrolytic aluminum anodes, which can protect the anode carbon block and the anode steel claw from oxidation and reduce loss as much as possible, while simplifying the preparation process and reducing the preparation cost. At the same time, due to the doping of graphene, the conductivity is improved, so the production energy consumption and cost of electrolytic aluminum can be reduced to a certain extent, and has a promising prospect for promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 A schematic flow chart of a method for preparing a high-conductivity, high-temperature, anti-oxidation and life-extending coating for electrolytic aluminum anodes provided by the present invention; Figure 2 The figure is a physical picture of the sample of the anode steel claw and the carbon block sprayed with the coating prepared in Example 1 of the present invention; Figure 3 This is a physical picture of a carbon block sprayed with the coating prepared in Example 1 of the present invention, which is undergoing testing. DETAILED DESCRIPTION
[0034] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0035] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.
[0036] The invention provides a high-conductivity, high-temperature, anti-oxidation and life-extending coating for electrolytic aluminum anodes, which is composed of the following raw materials by weight: 34-50 parts of refined bauxite; 20-25 parts of water; 20-30 parts of silicon carbide; 1.5-3 parts of graphene; 4-6 parts of glazing agent; 2.1-2.2 parts of film-forming agent; 0.3-0.4 parts of modifier; Among them, the aluminum oxide content in the refined bauxite is 97wt.%-99wt.%; the composition of the glaze former is calculated by weight percentage, talc is 32.5%-47.5%, albite is 52.5%-67.5%, and lanthanide oxide is 0.3%-0.7%; the film-forming agent is selected from one of polyurethane, polyacrylate, and polyvinyl pyrrolidone; the modifier is selected from one of silane coupling agent or sodium dodecylbenzene sulfonate.
[0037] The present invention will be further described below in conjunction with specific embodiments, but the present invention is not limited thereto.
[0038] The raw materials and their weight percentages involved in the embodiments and comparative examples of the present invention are shown in Table 1 below.
[0039] Table 1
[0040] In the above table, polyvinyl pyrrolidone is used as the film-forming agent, 3-(methacryloyloxy)propyltrimethoxysilane (silane coupling agent KH-570) is used as the modifier; the lanthanum oxide is selected from one or more combinations of lanthanum oxide, cerium oxide, neodymium oxide, and europium oxide, and the purity is not less than 99.9%.
[0041] Example 1 The present embodiment provides a high-conductivity, high-temperature, anti-oxidation and life-extending coating for electrolytic aluminum anodes, which is composed of the following raw materials, by weight: 46 parts of refined bauxite; 25 parts of water; 20 parts of silicon carbide; 2 parts of graphene; 4.4 parts of glazing agent; 2.2 parts of film-forming agent; and 0.4 parts of modifier.
[0042] The preparation method of the coating comprises the following steps: Step 1: ball milling the refined bauxite, setting the ball-to-material ratio to 5:1, using zirconia grinding balls with diameters of 5 mm, 7 mm and 12 mm, respectively, in a quantity ratio of 18:5:2 as the ball milling medium, and the ball milling time is 4 hours to obtain a ball milling product; mixing the ball milling product with a modifier, and coating and modifying it with a powder modifier, and the modification time is 1.5 hours to obtain a first product with a particle size of 450-600 meshes; Step 2: The first product is mixed with silicon carbide and graphene, and subjected to ball milling treatment. The ball-to-material ratio is set to 8:1, and zirconium oxide grinding balls with diameters of 1.4 mm, 1.6 mm and 2.5 mm are mixed in a quantity ratio of 45:20:5 as ball milling media. The ball milling treatment time is 5 hours, and a second product with a particle size of 650-750 mesh is obtained; Step 3: Mix the film-forming agent with water to obtain a film-forming agent solution; mix albite and talc, and use a 2PG-610X400 roller crusher to continuously crush them for 2 hours at a power of 30 kW, and then ball-mill the crushed products, setting the ball-to-material ratio to 3:1, and using stainless steel grinding balls with diameters of 6 mm, 8 mm and 10 mm, respectively, in a quantitative ratio of 11:5:0.8 as ball-milling media, and the ball-milling time is 1 hour to obtain a third product with a particle size of 750-950 meshes; Step 4: mixing the second product, the third product and the lanthanide oxide powder and adding the mixture into a film-forming agent solution to obtain a fourth product; Step 5: Place the fourth product in a closed environment with a pressure of 1.4 MPa, set the heating temperature to 150°C, the stirring speed during the heating process to 60 r / min, and the heating time to 3 hours, to obtain a high-conductivity, high-temperature, anti-oxidation and life-extending coating for the electrolytic aluminum anode.
[0043] Example 2 The present embodiment provides a high-conductivity, high-temperature, anti-oxidation and life-extending coating for electrolytic aluminum anodes, which is composed of the following raw materials, by weight: 40 parts of refined bauxite; 25 parts of water; 20 parts of silicon carbide; 3 parts of graphene; 4.6 parts of glazing agent; 2.1 parts of film-forming agent; and 0.3 parts of modifier.
[0044] The preparation method of the coating comprises the following steps: Step 1: ball milling the refined bauxite, setting the ball-to-material ratio to 5:1, using zirconia grinding balls with diameters of 5 mm, 7 mm and 12 mm respectively in a quantity ratio of 15:4:2 as ball milling media, the ball milling time is 2.5 hours, and a ball milling product is obtained; the ball milling product is mixed with a modifier, and a powder modifier is used for coating and modification, and the modification time is 1 hour to obtain a first product with a particle size of 450-600 meshes; Step 2: The first product is mixed with silicon carbide and graphene, and subjected to ball milling treatment. The ball-to-material ratio is set to 8:1, and zirconium oxide grinding balls with diameters of 1.4 mm, 1.6 mm and 2.5 mm are mixed in a quantity ratio of 40:15:3 as ball milling media. The ball milling treatment time is 4 hours, and a second product with a particle size of 650-750 mesh is obtained; Step 3: Mix the film-forming agent with water to obtain a film-forming agent solution; mix albite and talc, and use a 2PG-610X400 roller crusher to continuously crush them for 1 hour at a power of 25 kW, and then ball-mill the crushed products, setting the ball-to-material ratio to 3:1, and using stainless steel grinding balls with diameters of 6 mm, 8 mm and 10 mm, respectively, in a quantity ratio of 10:4:0.6 as ball-milling media, and the ball-milling time is 0.5 h to obtain a third product with a particle size of 750-950 meshes; Step 4: mixing the second product, the third product and the lanthanide oxide powder and adding the mixture into a film-forming agent solution to obtain a fourth product; Step 5: Place the fourth product in a closed environment with a pressure of 1.2 MPa, set the heating temperature to 130°C, the stirring speed during the heating process to 50 r / min, and the heating time to 2.5 h, to obtain a highly conductive, high-temperature, anti-oxidation and life-extending coating for the electrolytic aluminum anode.
[0045] Example 3 The present embodiment provides a high-conductivity, high-temperature, anti-oxidation and life-extending coating for electrolytic aluminum anodes, which is composed of the following raw materials, by weight: 50 parts of refined bauxite; 20 parts of water; 20 parts of silicon carbide; 1.5 parts of graphene; 6 parts of glazing agent; 2.1 parts of film-forming agent; and 0.4 parts of modifier.
[0046] The preparation method of the coating comprises the following steps: Step 1: ball milling the refined bauxite, setting the ball-to-material ratio to 5:1, using zirconia grinding balls with diameters of 5 mm, 7 mm and 12 mm respectively in a quantity ratio of 20:6:3 as ball milling media, the ball milling time is 4.5 hours, and a ball milling product is obtained; the ball milling product is mixed with a modifier, and a powder modifier is used for coating and modification, and the modification time is 2 hours to obtain a first product with a particle size of 450-600 mesh; Step 2: The first product is mixed with silicon carbide and graphene, and subjected to ball milling treatment. The ball-to-material ratio is set to 8:1, and zirconium oxide grinding balls with diameters of 1.4 mm, 1.6 mm and 2.5 mm are mixed in a quantity ratio of 55:23:7 as ball milling media. The ball milling treatment time is 6 hours, and a second product with a particle size of 650-750 mesh is obtained; Step 3: Mix the film-forming agent with water to obtain a film-forming agent solution; mix albite and talc, and use a 2PG-610X400 roller crusher to continuously crush them for 2 hours at a power of 35 kW, and then ball-mill the crushed products, setting the ball-to-material ratio to 3:1, and using stainless steel grinding balls with diameters of 6 mm, 8 mm and 10 mm, respectively, in a quantitative ratio of 12:6:1 as ball-milling media, and the ball-milling time is 1.5 hours to obtain a third product with a particle size of 750-950 meshes; Step 4: mixing the second product, the third product and the lanthanide oxide powder and adding the mixture into a film-forming agent solution to obtain a fourth product; Step 5: Place the fourth product in a closed environment with a pressure of 1.5 MPa, set the heating temperature to 170°C, the stirring speed during the heating process to 70 r / min, and the heating time to 3.5 h, to obtain a high-conductivity, high-temperature, anti-oxidation and life-extending coating for the electrolytic aluminum anode.
[0047] Example 4 The present embodiment provides a high-conductivity, high-temperature, anti-oxidation and life-extending coating for electrolytic aluminum anodes, which is composed of the following raw materials, by weight: 34 parts of refined bauxite; 25 parts of water; 30 parts of silicon carbide; 2.5 parts of graphene; 6 parts of glazing agent; 2.1 parts of film-forming agent; and 0.4 parts of modifier.
[0048] The preparation method of the coating comprises the following steps: Step 1: ball milling the refined bauxite, setting the ball-to-material ratio to 5:1, using zirconia grinding balls with diameters of 5 mm, 7 mm and 12 mm, respectively, in a quantity ratio of 18:5:2 as the ball milling medium, and the ball milling time is 4 hours to obtain a ball milling product; mixing the ball milling product with a modifier, and coating and modifying it with a powder modifier, and the modification time is 1.5 hours to obtain a first product with a particle size of 450-600 meshes; Step 2: The first product is mixed with silicon carbide and graphene, and subjected to ball milling treatment. The ball-to-material ratio is set to 8:1, and zirconium oxide grinding balls with diameters of 1.4 mm, 1.6 mm and 2.5 mm are mixed in a quantity ratio of 45:20:5 as ball milling media. The ball milling treatment time is 5 hours, and a second product with a particle size of 650-750 mesh is obtained; Step 3: Mix the film-forming agent with water to obtain a film-forming agent solution; mix albite and talc, and use a 2PG-610X400 roller crusher to continuously crush them for 2 hours at a power of 25-35kW, and then ball-mill the crushed products, setting the ball-to-material ratio to 3:1, and using stainless steel grinding balls with diameters of 6 mm, 8 mm and 10 mm, respectively, in a ratio of 11:5:0.8 as ball-milling media, and the ball-milling time is 1 hour to obtain a third product with a particle size of 750-950 meshes; Step 4: mixing the second product, the third product and the lanthanide oxide powder and adding the mixture into a film-forming agent solution to obtain a fourth product; Step 5: Place the fourth product in a closed environment with a pressure of 1.4 MPa, set the heating temperature to 150°C, the stirring speed during the heating process to 60 r / min, and the heating time to 3 hours, to obtain a high-conductivity, high-temperature, anti-oxidation and life-extending coating for the electrolytic aluminum anode.
[0049] Comparative Example This comparative example provides an electrolytic aluminum anode coating, which is composed of the following raw materials, by weight: 57 parts of refined bauxite, 31.5 parts of water, 6 parts of glazing agent (4.02 parts of albite, 1.95 parts of talc, 0.03 parts of lanthanide oxide), 5.1 parts of film-forming agent, and 0.4 parts of modifier.
[0050] The preparation method of the coating comprises the following steps: Step 1: ball milling the refined bauxite, setting the ball-to-material ratio to 5:1, using zirconia grinding balls with diameters of 5 mm, 7 mm and 12 mm, respectively, in a quantity ratio of 18:5:2 as the ball milling medium, and the ball milling time is 4 hours to obtain a ball milling product; mixing the ball milling product with a modifier, and coating and modifying it with a powder modifier, and the modification time is 1.5 hours to obtain a first product with a particle size of 450-600 meshes; Step 2: Mix the film-forming agent with water to obtain a film-forming agent solution; mix albite and talc, and use a 2PG-610X400 roller crusher to continuously crush them for 2 hours at a power of 30 kW, and then ball-mill the crushed products, setting the ball-to-material ratio to 3:1, and using stainless steel grinding balls with diameters of 6 mm, 8 mm and 10 mm, respectively, in a quantitative ratio of 11:5:0.8 as ball-milling media, and the ball-milling time is 1 hour to obtain a second product with a particle size of 750-950 meshes; Step 3: mixing the first product, the second product and lanthanide oxide powder and adding the mixture into a film-forming agent solution to obtain a third product; Step 4: Place the third product in a closed environment with a pressure of 1.4 MPa, set the heating temperature to 150°C, the stirring speed during the heating process to 60 r / min, and the heating time to 3 hours to obtain the electrolytic aluminum anode coating.
[0051] Application performance testing The coating prepared in Example 1 of the present invention is sprayed onto the surface of the anode carbon block and the anode steel claw, respectively. The coating thickness on the surface of the anode carbon block is 0.9 mm, and the coating thickness on the surface of the anode steel claw is 0.7 mm. The anode carbon block and the anode steel claw coated with the coating are tested for application performance. The test items include high temperature burning test, cryolite oxidation test, conductivity test, adhesion performance, aluminum liquid contamination degree and service life. The specific test methods and test results are as follows: The experiment was conducted in a 350KA electrolytic cell of an aluminum power enterprise in Ningxia. After testing, the coating prepared by the present invention adhered well to the carbon block and the anode steel claw, and the surface was smooth without obvious holes or cracks. Figure 2 The service life of the carbon block without the coating of the present invention is 27-28 days, and the service life of the carbon block with the coating of the present invention is 30-31 days, and it maintains good working condition after spraying, as shown in the attached Figure 3 The following are the specific test process and data: Three carbon blocks sprayed with the coating prepared in Example 1 of the present invention were numbered A1, A2, and A3, and three carbon blocks not sprayed with the coating were numbered AA1, AA2, and AA3, and were placed in a muffle furnace together. The temperature was controlled at about 970° C. After calcination for 10 hours, the weight loss of the carbon blocks was measured. It was found that the carbon blocks not sprayed with the coating had a larger weight loss, while the carbon blocks sprayed with the coating had a smaller weight loss. The specific weight loss rates are shown in Table 2 below: Table 2
[0052] Three carbon blocks sprayed with the coating prepared by the present invention were numbered B1, B2, and B3, and three carbon blocks not sprayed with the coating were numbered BB1, BB2, and BB3, and were placed in a muffle furnace together. Each group of carbon blocks was buried in 1000.0g of cryolite and burned at 970°C. After 8 hours, the corrosion of the carbon blocks placed on the cryolite surface was observed. It was found that the upper surface of the carbon blocks sprayed with the coating was less corroded, only the coating was partially corroded, and the corrosion of the carbon block substrate was relatively slight, while the upper surface of the carbon blocks not sprayed with the coating was more seriously corroded. The specific corrosion weight loss rate is shown in Table 3 below: Table 3
[0053] The three carbon blocks sprayed with the coating of the present invention are numbered C1, C2, and C3 respectively, the three carbon blocks sprayed with the coating prepared in the above comparative example are numbered CC1, CC2, and CC3 respectively, and the carbon blocks not sprayed with any coating are numbered CCC1, CCC2, and CCC3. The two ends of these carbon blocks are connected to two electrodes respectively, and then the carbon blocks are connected to a 350kA constant current source respectively. The voltage at both ends of the carbon blocks is measured each time. The voltage averages of the three groups sprayed with the coating prepared in the present invention, the three groups sprayed with the above comparative example coating, and the three groups not sprayed with coating are compared. It is found that the voltage of the group sprayed with the coating prepared in the present invention is lower than that of the other two groups. Due to the enhanced conductivity, the voltage on both sides will decrease when the current is constant. The specific voltage values are shown in Table 4 below: Table 4
[0054] Six carbon blocks sprayed with the coating prepared in Example 1 of the present invention were numbered D1, D2, D3, D4, D5, and D6, and the adhesion was tested according to the national standard GB / T 5210. The test results all reached level 0. The test results are shown in Table 5 below: Table 5
[0055] Three carbon blocks sprayed with the coating prepared in Example 1 of the present invention were numbered E1, E2, and E3, and the carbon blocks not sprayed with the coating of the present invention were numbered EE1, EE2, and EE3, and were respectively installed on the anode steel claws (the surface of the anode steel claws was coated with the coating prepared in Example 1 of the present invention, and the coating thickness was 0.7 mm) prepared from low-carbon steel and waste steel claws by melting and casting. Since this test is a destructive test, the service life test was carried out while characterizing the degree of aluminum liquid contamination. On the 7th day, the degree of aluminum liquid contamination was characterized, and it was found that the aluminum of the electrolytic cell sprayed with the coating of the present invention was of higher quality and less impurity elements, and the anode steel claws were exposed on the 30th-31st day, while the carbon blocks not sprayed with the coating had exposed the anode steel claws on the 27th-28th day. The working time of the samples and the test results are shown in Tables 6 and 7 below, respectively: Table 6
[0056] Table 7
[0057] In summary, The high-conductivity, high-temperature, anti-oxidation and life-extending coating for electrolytic aluminum anodes provided by the present invention has strong adhesion and is coated on the surface of anode carbon blocks and anode steel claws, which can significantly reduce the thermal weight loss of anode carbon blocks and anode steel claws and improve the corrosion resistance and conductivity of both. The high-conductivity, high-temperature, anti-oxidation and life-extending coating for electrolytic aluminum anodes provided by the present invention is applied to the electrolytic aluminum production process, which can reduce the impurity content in aluminum liquid, ensure the quality of aluminum liquid, and protect the anode carbon blocks and anode steel claws from being oxidized and reducing losses as much as possible, while extending the service life of the two, reducing production energy consumption and costs, and has a prospect for promotion and application.
[0058] The above are only preferred embodiments of the present invention, and are not intended to limit the implementation methods and protection scope of the present invention. Those skilled in the art should be aware that all solutions obtained by equivalent substitutions and obvious changes made using the contents of the specification of the present invention should be included in the protection scope of the present invention.
Claims
1. A high-conductivity, high-temperature, anti-oxidation and life-extending coating for electrolytic aluminum anode, characterized in that: By weight, it is composed of the following raw materials: 34-50 parts of refined bauxite; 20-25 parts of water; 20-30 parts of silicon carbide; 1.5-3 parts of graphene; 4-6 parts of glaze former; 2.1-2.2 parts of film former; 0.3-0.4 parts of modifier; The glaze former is composed of albite, talc and lanthanide oxides, and the content of lanthanide oxides in the glaze former is 0.3wt.%-0.7wt.%.
2. The coating according to claim 1, characterized in that The aluminum oxide content in the refined bauxite is 97wt.%-99wt.%.
3. The coating according to claim 1, characterized in that The composition of the glaze forming agent is calculated by weight percentage, wherein talc is 32.5%-47.5%, albite is 52.5%-67.5%, and lanthanide oxide is 0.3%-0.7%.
4. The coating according to claim 1, characterized in that The film-forming agent is selected from one of polyurethane, polyacrylate and polyvinyl pyrrolidone.
5. The coating according to claim 1, characterized in that The modifier is selected from a silane coupling agent or sodium dodecylbenzene sulfonate.
6. A method for preparing a coating according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1, ball-milling the refined bauxite, mixing the ball-milled product with a modifier, and coating and modifying the product to obtain a first product; S2, mixing the first product with silicon carbide and graphene, and subjecting the mixture to ball milling to obtain a second product; S3, mixing the film-forming agent with water to obtain a film-forming agent solution; mixing albite and talc, crushing and ball-milling to obtain a third product; S4, mixing the second product, the third product and lanthanide oxide powder and adding the mixture to a film-forming agent solution to obtain a fourth product; S5. Place the fourth product in a sealed pressurized environment, heat and mix for a certain period of time, and obtain a coating for electrolytic aluminum anode with high conductivity, high temperature, anti-oxidation and life extension.
7. The preparation method according to claim 6, characterized in that: The particle size of the first product is 450-600 mesh, the particle size of the second product is 650-750 mesh, and the particle size of the third product is 750-950 mesh.
8. The preparation method according to claim 6, characterized in that In step S5, the pressure is 1.2-1.5 MPa, the heating temperature is 130-170° C., the mixing stirring speed is 50-70 r / min, and the heating time is 2.5-3.5 h.
9. Application of a coating for high conductivity, high temperature, anti-oxidation and life extension of electrolytic aluminum anode, the coating being a coating according to any one of claims 1 to 5, or a coating prepared by the preparation method according to any one of claims 6 to 8, characterized in that: The coating is attached to the surface of the anode carbon block and / or the anode steel claw by spraying.
10. The use according to claim 9, characterized in that: The coating is attached to the surface of the anode carbon block and the anode steel claw by spraying; the anode carbon block is made of anthracite and metallurgical coke as main raw materials and coal tar as a modifier; the anode steel claw is made of low-carbon steel and waste steel claws by smelting and casting.
Citation Information
Patent Citations
Cathode block having an abrasion-resistant surface that can be wetted
CN105026619A
Novel energy-saving corrosion-resistant anode steel claw for electrolyzing aluminum and design method thereof
CN109898101A
Prebaked anode anti-oxidation coating for electrolytic aluminum and preparation method of prebaked anode anti-oxidation coating
CN115895302A
Coating for aluminum electrolysis carbon anode, preparation method of coating and aluminum electrolysis carbon anode
CN118388986A
Electrodes for supercapacitor comprising reduced graphene oxide, method of manufacturing the electrodes, and super capacitor comprising the electrodes
KR102333731B1
Cited By
High-temperature-resistant and high-conductivity steel for electrolytic aluminum anode steel claw and preparation method
CN119980067A
High-temperature-resistant and high-conductivity steel for electrolytic aluminum anode steel claw and preparation method thereof
CN119980067B
Heat-preservation anti-oxidation coating for anode carbon block and preparation method of heat-preservation anti-oxidation coating
CN119980360A